Mali : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2014)
This paper reviews Mali's 2012-2017 Poverty Reduction and Growth Strategy Paper. Mali's GDP was CFAF 1,741.89 billion in 2012; real growth was ?1.2 percent, that is, excluding inflation (2.7 percent in 2011). The decline of 3.9 points in growth between 2011 and 2012 was finally stemmed, despite the major shocks that Mali had to face in 2012. The dual security and institutional shock had a negative impact on the entire economy, and more particularly on certain subsectors such as construction and public works, the hotel industry, and commerce. The GDP growth rate was ?1.2 percent in 2012, compared with 2.7 percent in 2011.